2016
DOI: 10.1044/2016_ajslp-15-0135
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Language Action Therapy in Chronic Aphasia: A Randomized Clinical Trial Examining Guidance by Constraint

Abstract: Purpose Intensive language action therapy (ILAT) can be effective in overcoming learned nonuse in chronic aphasia. It is suggested that all three guiding principles (constraint, communication embedding, massed practice) are essential to ILAT's success. We examined whether one of these, guidance by constraint, is critical. Method Twenty-four participants with aphasia (PWAs) were assigned to ILAT or a modified version of promoting aphasic communicative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 57 publications
1
29
0
11
Order By: Relevance
“…Ciccone N et al [ 35 ] did not find the superiority of distributed CIAT (45–60 minutes/session, 20 sessions for 5 weeks) over the control training with the same dosage for stroke patients at very acute phase. Sickert A et al [ 31 ] found both groups showed improvement compared with the baseline, however, no significant difference was noted in any outcomes between two group, which was similar in the study of Kurland et al Wilssens I et al [ 30 ] showed that the CIAT positively affected the language production and phonology, while the group of BOX posed more beneficial effects on the language comprehension and semantics, and Kurland J et al [ 42 ] found that the CIAT gained better generalization into the untrained words, compared with the PACE group, in picture naming (23.4% for CIAT and 15.2% for PACE, p <0.001) ( Table 2 ).…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…Ciccone N et al [ 35 ] did not find the superiority of distributed CIAT (45–60 minutes/session, 20 sessions for 5 weeks) over the control training with the same dosage for stroke patients at very acute phase. Sickert A et al [ 31 ] found both groups showed improvement compared with the baseline, however, no significant difference was noted in any outcomes between two group, which was similar in the study of Kurland et al Wilssens I et al [ 30 ] showed that the CIAT positively affected the language production and phonology, while the group of BOX posed more beneficial effects on the language comprehension and semantics, and Kurland J et al [ 42 ] found that the CIAT gained better generalization into the untrained words, compared with the PACE group, in picture naming (23.4% for CIAT and 15.2% for PACE, p <0.001) ( Table 2 ).…”
Section: Resultssupporting
confidence: 58%
“…One study [ 41 ] compared the therapist-led and layperson-led CIAT, so we excluded it. Finally, eight RCTs were included in this review [ 19 , 27 31 , 35 , 42 ]. ( Fig 1 )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These protocols share the following defining characteristics: (1) Treatment is delivered in small groups (up to three patients); (2) practice is strictly focused on a verbal, spoken output with other forms of communication either not practiced or actively discouraged (constrained); (3) treatment is intensive where intensity refers to the therapy being delivered both with a high-dose and in a compact way (massed rather than distributed practice); (4) treatment is focused on word production (picture naming); (5) treatment involves shaping, where word production is practiced repeatedly, with different carrier sentences, and different degrees of facilitation; (6) naming is promoted in the context of social requests as part of a card game (Go Fish) where participants ask other participants for matching cards. CIP have received a lot of attention because studies have shown benefits for treated words and, occasionally, improvements on standardized tasks (e.g., Carpenter & Cherney, 2016;Pulvermüller et al, 2001; for a review, see Zhang et al, 2017; but also see for negative results-Attard, Rose, & Lanyon, 2012;Hameister, Nickels, Ca, & Croot, 2017;Kurland, Stanek, Stokes, Li, & Andrianopoulos, 2016;Nickels & Osborne, 2016). Which elements are responsible for the success of CIP, however, remain unclear.…”
Section: Background and Rationalementioning
confidence: 99%